Representing and Implementing Moral Values to Foreign Students in Indonesian Textbooks for Learners Other Than Indonesians - Yuni Pratiwi; Kusubakti Andajani; Imam Suyitno; Asri Ismail; Bambang Prastio (Universitas Negeri Makassar, 2023)
The textbook